A Comparison of Automated and Manifest Refraction: The Effect of Age - Sohail Ahmed, Jehangir Durrani, Khayyam Durrani, Amanullah Khan (Pakistan Journal of Ophthalmology, 2006)
Purpose: Autorefraction without subjective refinement is being increasingly employed by opticians in Pakistan for prescribing glasses. The purpose of this study is to compare the refractive correction obtained by autorefraction alone and manifest refraction at a tertiary care hospital in Pakistan and to determine the relationship of this difference with age. Material and Methods: Two hundred and sixty nine patients visiting the ophthalmology clinic of a large tertiary-care hospital in Karachi, Pakistan were studied. Autorefraction alone using a Canon R-10 Autorefractor and manifest refraction were performed at the same visit. A clinically significant difference between autorefraction and manifest refraction was defined as a difference of >0.50 D in sphere, cylinder, spherical equivalent or weighted axis, or >10° in axis. Results: In 266 right eyes, the median difference between autorefraction and manifest refraction in spherical corrections was +0.01 D (p=0.85), -0.33 D in cylindrical corrections (p<0.01), 10° in axes (p<0.01), and –0.16 D in spherical equivalent (p=0.02). Children 10 years of age or younger were 2.23 times more likely to have a clinically significant difference in spherical corrections (OR: 2.23, 95% CI: 1.12-4.47).Comparable results were observed for the left eye. Conclusions: There is a significant difference between the corrections obtained by autorefraction alone and manifest refraction, particularly in children. Autorefraction alone without subjective refinement cannot be substituted for manifest refraction, especially in children 10 years of age or younger.